Local Community’s Perception towards a Protected Area in the Shivalik Landscape, India - Rana, Sakshi; Kumari, Priti; Badola, Ruchi; Hussain, Syed Ainul (Indian Forester, 2025)
In Global South, Protected Areas (PAs) in human-dominated landscapes create unavoidable trade offs between biodiversity conservation and local livelihoods. The authors surveyed 157 respondents adjacent to Kalesar National Park and Wildlife Sanctuary (KNPWLS) in Shivalik Landscape, India to assess perceived benefits and costs of living near the PA and perception towards it. Overall, 81.5% of respondents recognized Kalesar Forest as a PA, while about 78% of them supported the continued existence of the PA. Perceived benefits centred on access to fuelwood, fodder and other forest products. The principal costs were crop and livestock losses attributable to wild animals. Despite these recurrent losses, most respondents maintained positive attitudes toward conservation, suggesting that support can be sustained when livelihood needs are acknowledged and addressed. These findings highlight the need for locally tailored co management strategies that extend tangible benefits, such as equitable tourism revenue, alternative fodder sources and rapid compensation for wildlife damage to the most vulnerable groups. By shifting from top down enforcement to participatory governance and targeted benefit sharing, managers can foster durable community support and reconcile conservation goals with human well being across densely settled PA landscapes in South Asia.